The Anti-atherogenic Role of Exercise Is Associated With the Attenuation of Bone Marrow-Derived Macrophage Activation and Migration in Hypercholesterolemic Mice - Rentz, Thiago; Wanschel, Amarylis C. B. A.; de Carvalho Moi, Leonardo; Lorza-Gil, Estela; de Souza, Jane C.; dos Santos, Renata R.; Oliveira, Helena C. F. (Frontiers in Physiology, 2020)
An early event in atherogenesis is the recruitment and infiltration of circulating monocytes and macrophage activation in the subendothelial space. Atherosclerosis subsequently progresses as a unresolved inflammatory disease, particularly in hypercholesterolemic conditions. Although exercise training has been a widely accepted strategy to inhibit atherosclerosis, the impact of exercise on arterial wall inflammation and macrophage phenotype and function has not yet been directly evaluated. Thus, the aim of this study was to investigate the effects of chronic exercise on the inflammatory state of atherosclerotic lesions with a focus on macrophages. Hypercholesterolemic LDL-receptor-deficient male mice were subjected to treadmill training for 8 weeks and fed a high-fat diet. Analyses included plasma lipoprotein and cytokine levels; aortic root staining for lipids (oil red O); macrophages (CD68, MCP1 and IL1β), ); oxidative (nitrotyrosine and, DHE) and endoplasmic reticulum (GADD) stress. Primary bone marrow-derived macrophages (BMDM) were assayed for migration activity, motility phenotype (Rac1 and F-actin) and inflammation-related gene expression. Plasma levels of HDL cholesterol were increased, while levels of proinflammatory cytokines (TNFa, IL1b, and IL6) were markedly reduced in the exercised mice. The exercised mice developed lower levels of lipid content and inflammation in atherosclerotic plaques. Additionally, lesions in the exercised mice exhibited fewer oxidative and ER stress markers. BMDM isolated from the exercised mice showed a marked reduction in proinflammatory cytokine gene expression and migratory activity and a disrupted motility phenotype. More importantly, bone marrow from exercised mice transplanted into sedentary mice led to reduced atherosclerosis in the recipient mice, thus suggesting that epigenetic mechanisms are associated with exercise. Collectively, the presented data indicate that exercise training prevents atherosclerosis by inhibiting bone marrow-derived macrophage recruitment and activation.